Penambahan Vitera Plus Dalam Air Minum Terhadap Pertambahan Berat Badan Ayam Pedaging: The Addition of Vitera Plus in Drinking Water Against Broiler Weight Gain - Warso, Dwijo; Herawati, Herawati (Jurnal Riset Agribisnis dan Peternakan, 2023)
The development of the broiler business is very volatile due to relatively unstable meat prices and high feed prices. One product to increase the level of broiler feed efficiency is to provide viterna plus. The purpose of this study was to determine the level of viterna plus in drinking water on the growth of broiler chicken weight. The material in this study was 100 DOC strains CP 707. Treatment Ro = viterna plus 0 cc/liter, R1 = plus 1 cc/liter, R2 = viterna plus 2 cc/liter, R3 = viterna plus 3 cc/liter. Weight gain in the first week there was a marked difference (P<0.05) where R0 was different from R2, but R1 and R3 were not significantly different from R0 or R2. Weight gain at weeks 2 to 6 is no different. In general, giving viterna plus has a very small effect, this is seen with low to high levels, namely in R1, R2 and R3 are no different. The conclusion is that the addition of viterna plus given through broiler chicken drinking water at a usage rate of 2 cc/head can improve weight gain.    It is recommended to use 2 cc / head in order to increase daily weight gain, adding more than 2 cc / head does not increase weight gain.